Foundations of wellness - Reger-Nash, Bill 1942-; Juckett, Gregory 1955-; Smith, Meredith 1981- (Human Kinetics, 2015)
Life is crammed with busyness, screen time, and an abundance of shallow experiences. If you don't mindfully change your way of thinking and behaving, that's all your life will ever be. Foundations of Wellness can help you live a satisfying life--one full of rich and deep experiences. You'll understand your identity and inner strengths and resources as well as set and move toward meaningful personal goals. With Foundations of Wellness, you will explore physical, mental, emotional, social, environmental, and spiritual realms of wellness using an evidence-based approach to health and wellness that will help you explore ways to live your life to the fullest. You will examine the seven attitudinal foundations of mindfulness to daily living, delve into wellness resources and dietary needs, discover health check strategies, and learn the keys to making healthy behavioral changes. Foundations of Wellness is written in a conversational style and divided into three parts. Part I establishes basic wellness problems and introduces tools to discovering wellness and inner peace. Part II addresses physical dimensions of wellness, including physical activity, nutrition, sleep, and body maintenance. In part III you'll discover the strategies that will propel you to a higher level of living--one that can affect not only your life but also the lives of others for generations to come. Each chapter explores key concepts and topics that affect your wellness. The chapters begin with objectives and a vignette that illustrates a challenge related to the content and use stories to illustrate teaching points. The text also incorporates activity sidebars that empower you to make the behavioral changes that will lead to a more satisfying and meaningful life. You will learn how to incorporate mindfulness--a practice that helps you live with greater awareness--and positive psychology as you embark on your wellness journey. In Foundations of Wellness, you will also learn the seven attitudinal foundations of mindfulness practices and explore the spiritual truths that are at the core of wellness